Prevalence of hypertension in rural population of Central India - Singh, P. S.; Singh, Prafulla K.; Zafar, Khwaja S.; Sharma, Himanshu; Yadav, Sudhir K.; Gautam, Rajesh K.; Pious, Tony (International Journal of Research in Medical Sciences, 2017)
Background: Hypertension is an important public health problem in both rural and urban areas of economically developed as well as developing nations. It is a chronic medical condition and is one of the most common life threatening non-communicable disease. It is an asymptomatic condition, symptoms do not arise unless the complications develop which result in delayed diagnosis and treatment especially among the uneducated and unexplained social groups such as rural population. Present study was an attempt to provide data on hypertension in rural area of central India. The objective of present study was to estimate the prevalence of hypertension in rural population above 18 years of age in Etawah and neighbouring districts of Uttar Pradesh, India. Methods: The study was planned to determine the prevalence of hypertension in rural community by health camp and door to door approach. BP measurements were made after the subject had rested for at least 5 minutes in a seated position using mercury sphygmomanometer. The first blood pressure measurement was taken after obtaining socio-demographic information from the study subject, while the second was recorded after 5 minutes. Results: The prevalence of hypertension was found to be 17%, which was observed to be higher among female i.e. 170 (18.3%) individuals than males 153 (15.8%) individuals. The prevalence of hypertension was observed to be higher among the older individuals. It was found to be 5.26 times higher in older (>50 years) than the younger (<30 years) age group. We found prehypertension in 65.74%, Stage I hypertension in 11.33% and stage II hypertension in 5.69% individuals. Conclusions: Present study showed that high prevalence of hypertension in rural area of Western Uttar Pradesh, Central India.